Antibodies to Infliximab and Adalimumab in Patients with Rheumatoid Arthritis in Clinical Remission: A Cross-Sectional Study. (11th February 2015) - Eng, Grith P.; Bendtzen, Klaus; Bliddal, Henning; Stoltenberg, Michael; Szkudlarek, Marcin; Fana, Viktoria; Lindegaard, Hanne M.; Omerovic, Emina; Højgaard, Pil; Jensen, Elmo K.; Bouchelouche, Pierre N.
Abstract : Objective . To investigate if antibodies towards biological TNF- α inhibitors (anti-TNFi Abs) are present in patients with rheumatoid arthritis (RA) in clinical remission and to relate any anti-TNFi Abs to circulating level of TNF- α inhibitor (TNFi). Methods . Patients with RA, treated with infliximab or adalimumab, and in clinical remission (DAS28(CRP) < 2.6) were included from 6 out-patient clinics. In blood samples, presence of anti-TNFi Abs was determined by radioimmunoassay, and concentration of bioactive TNFi was measured by a cell-based reporter gene assay. Results . Anti-TNFi Abs were present in 8/44 patients (18%) treated with infliximab and 1/49 patients (2%) treated with adalimumab (p = 0.012 ). In the former group, anti-TNFi Abs corresponded with low levels of TNFi (p = 0.048 ). Anti-TNFi Ab-positive patients had shorter disease duration at initiation of TNFi therapy (p = 0.023 ) but were similar for the rest of the compared parameters. Conclusions . In RA patients in clinical remission, anti-TNFi Abs occur frequently in patients treated with infliximab, while they occur rarely in patients treated with adalimumab. Presence of anti-infliximab Abs is accompanied by low or undetectable levels of infliximab. These data suggest that continued infliximab treatment may be redundant in a proportion of RA patients treated with infliximab and in clinical remission.